PENGELOLAAN HUBUNGAN SEKOLAH DAN MASYARAKAT UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR (Universitas Negeri Semarang, 2021)
This study purpose to determine (1) the nature of the management of school and community relations, (2) the purpose, function and benefits of school and community relations, (3) the principles in management school and community relations, (4) the scope of scool relationship management and community in elementary schools, (5) the implementation of school and community relations program is carried out using alternative techniques (electronic media) in order to adapt to the development of the times. The method used is literature study method, by collecting library data, reading, taking notes and management research materials. The results show that the function of management school and community relationship can build the quality of education, especially at the elementary school level, increase community participations in the process of achieving school programs, with managemen it can increase cooperation between school and community relations. Its implementation includes various meetings, deliberations an the existence of cooperations between educational institutions and the surrounding community, besides that it can establish a close relationship between residents around the school to maintain security, involve community members in the school environment and vice versa, and carry out guidance for elementary school (SD). Evaluation is carried out on the management of school and community relations, namely parents are involved in management, the creation of new work programs, running process and sharing between parents. Â